2003
DOI: 10.1038/nature01681
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation state of the active-site cysteine in protein tyrosine phosphatase 1B

Abstract: Protein tyrosine phosphatases regulate signal transduction pathways involving tyrosine phosphorylation and have been implicated in the development of cancer, diabetes, rheumatoid arthritis and hypertension. Increasing evidence suggests that the cellular redox state is involved in regulating tyrosine phosphatase activity through the reversible oxidization of the catalytic cysteine to sulphenic acid (Cys-SOH). But how further oxidation to the irreversible sulphinic (Cys-SO2H) and sulphonic (Cys-SO3H) forms is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
525
2
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 602 publications
(542 citation statements)
references
References 22 publications
12
525
2
3
Order By: Relevance
“…One of the mechanisms involves the reaction of cysteine residue oxidized to sulfenic acid with an amide from the protein backbone. This reaction has been observed in purified proteins and in absence of glutathione in several PTPs (27,75). Thus, while feasible, this reaction has not yet been demonstrated to occur in vivo.…”
Section: A Signaling Proteins In Which Critical Cysteines Are Modifiedmentioning
confidence: 96%
See 4 more Smart Citations
“…One of the mechanisms involves the reaction of cysteine residue oxidized to sulfenic acid with an amide from the protein backbone. This reaction has been observed in purified proteins and in absence of glutathione in several PTPs (27,75). Thus, while feasible, this reaction has not yet been demonstrated to occur in vivo.…”
Section: A Signaling Proteins In Which Critical Cysteines Are Modifiedmentioning
confidence: 96%
“…Apart from glutathionylation, another chemical modification to prevent cysteine overoxidation has recently been discovered in the form of sulfenyl-amide formation. It was shown that, the cysteine residue in protein tyrosine phosphatase 1B (PTP1B) can react after oxidation to a sulfenic acid by H 2 O 2 in the absence of GSH (26,27). The sulfenic acid reacts further with an amide nitrogen of the backbone to form a cyclic sulfenyl-amide.…”
Section: <6>mentioning
confidence: 99%
See 3 more Smart Citations